Práticas corporais afro-brasileiras em uma realidade quilombola no Paraná: perspectivas de uma ação interventora - Gonçalves, Gislaine (2012)
The present study analyses how the Afro-Brazilian body practice is developed in a quilombola community in Paraná, and how it is built in social intervention actions. It was particularly necessary to: (a) foster reflections on the condition of being quilombola identifying how the Afro-Brazilian body practice occurs in the quilombola community of Invernada Paiol de Telha, in Guarapuava, Paraná; (b) to understand the process of building Afro-Brazilian body practice by quilombola who take part in the Afro-Kundun Balê Music and Dance Company; (c) to verify how the Afro-Brazilian body practice carried out by the group in study is set as social intervention actions. The research was developed based on ethnography guidance, along with social actors from the quilombola community of Invernada Paiol de Telha and, remarkably, with members of Afro Kundun Balê Music and Dance Company. The data gathering was carried out in four phases during the years of 2010 and 2011, with a total of 50 days of field immersion. As techniques to gather information we used image recording (movies and photographs), observation, semi-structured interview and notes from field journal. Through this study we conclude that the condition of "being quilombola" is not related to the color of the skin, but to the seclusion and barbarism the quilombola and their descendants went through. The Afro-Brazilian body practice which composed this history was overshadowed by other means of life and religion expressions, being deprived from Paiol de Telha daily life and limited to actions of members from Afro Kundun Balê Music and Dance Company and their assistants. The work developed by this groups is about human training for youngsters and adolescents through art, intervention in community with actions towards the awareness on the condition of being quilombola and the necessity of relive Afro-Brazilian body practice, being accepted but also refused due to its bond with Candomblé. The role of the group goes beyond the community and brings the Afro-Brazilian culture to many sorts of social interactions, fostering a critical and political thinking about the quilombola life style, demanding actions which bring up interventions in Paiol de Telha aiming to a development and an improvement of its inhabitants conditions.